Morphological variability of Euphorbia sepium N.E. Br. across the Sudanian and Sudano-Guinean zones of Benin Republic (West Africa): Implications for conservation. - ADOUKONOU-SAGBADJA, Hubert (My University, 2022)
Euphorbia sepium is a galactogenic plant used by livestock farmers in Benin to improve milk production in cows. Despite its proven medicinal and ethnobotanical importance, little is known about its morphological diversity. To assess the morphological diversity of E. sepium in the Sudanian and Sudano-Guinean zones of Benin, fifteen traits including eight quantitative and seven qualitative were studied on 54 individuals of this species. A Principal Component Analysis, a Hierarchical Ascending Classification, an analysis of variance of data and a Pearson linear correlation were performed to describe the intraspecific and inter-region diversity. The results exhibited significant variability in the morphological traits. Also, most of the traits showed a coefficient of variations higher than 30 %, revealing a high level of morphological diversity within the species. Three clusters with distinct phenotypic attributes were identified regardless the climatic zones considered. The major discriminating morphological traits include total plant height, crown height, collar diameter, number of stems, leaf width and length, and petiole length. Individuals in cluster 3 had the highest values of total height (6.94 ± 0.49 m), crown height (5.15 ± 1.42 m), collar diameter (24.45 ± 19.46 cm) and number of stems while those in cluster 1 showed the highest values for leaf length (6.88 ± 0.36 cm), leaf width (3.11 ± 0.46 cm) and petiole length (0.61 ± 0.12 cm). The study also revealed significant and positive correlation between plant height and crown height (r = 0.86; p < 0.001), plant height and collar diameter (r = 0.57; p < 0.001), plant height and number of stems (r = 0.49; p < 0.001). Also, between leaf length and width, leaf width and petiole length, we found a significant and positive correlation. This study provided useful information on the phenotypic variability of E. sepium and can be base for future conservation, domestication, and breeding programs.
Keywords: Benin; Conservation; Euphorbia sepium; Galactogenic plant; Morphological diversity